Native Endophytes of Tripterygium wilfordii-Mediated Biotransformation Reduces Toxicity of Celastrol - Ma, Ping-yang; Geng, Wei-ling; Ji, Hong-yan; Yue, Bang-wen; Liu, Cheng; Wang, Sa; Jiang, Zhi-bo; Chen, Jing; Wu, Xiu-li (Frontiers in Microbiology, 2022)
Celastrol (1), from the roots of Tripterygium Wilfordi Hook F, is most likely to become an anti-tumor drug, but with severe cytotoxicity. Due to the lack of modifiable sites in the structure of celastrol, the structural diversity of the modified products obtained by synthesis in the previous studies is insufficient, which hinders the pace of its patent medicine. This paper describes a method of microbial transformation to increase the modification site of celastrol and reduce its toxicity. The screening of Endophytes from native plants was introduced in this context, which led to found two novel stereoselective oxidation products as S-16-hydroxyl celastrol (2) and A-ring aromatized S-16-hydroxyl celastrol (3), along with a rare 7,9-octadecadienoic acid ester of celastrol (4). Their structures were determined by extensive spectroscopic data analysis, especially 1D and 2D NMR. Compared to 1, the compounds of 3 and 4 exhibited similar anti-tumor activity in U251, A549, KG-1 and B16 cell lines, and 2 had slightly lower anti-tumor activity comparing with 1. Furthermore, 2-4 showed lower cytotoxicity against BV-2 (about 21-fold lower, 2-92.82 μM, 3-34.25 μM, and 4-74.75 μM vs celastrol-4.35 μM), and the same trend against H9c2 and PC12 cell lines.